Studies of Kinetic Polymerization of Pectin-g-polyAAm in Homogeneous Solution - Sadeghi, Mohammad; Safari, Soudeh; Shahsavari, Hadis; Sadeghi, Hossein; Soleimani, Fatemeh (Asian Journal of Chemistry, 2013)
In this work, we have focused on study of kinetics of polymerization of graft copolymerization pectin and acrylamide (AAm) in a homogeneous solution. The relation kinetics of polymerization pectin-g-polyAAm with effective parameters was investigated as well. The kinetics of the graft copolymerization showed a second order kinetics of reaction. In addition, the effect temperature onto polymerization was also studied.